A review of piezoelectric polymers as functional materials for electromechanical transducers - Ramadan, Khaled S; Sameoto, D; Evoy, S (Smart materials and structures, 2014)
Polymer based MEMS and microfluidic devices have the advantages of mechanical flexibility, lower fabrication cost and faster processing over silicon based ones. Also, many polymer materials are considered biocompatible and can be used in biological applications. A valuable class of polymers for microfabricated devices is piezoelectric functional polymers. In addition to the normal advantages of polymers, piezoelectric polymers can be directly used as an active material in different transduction applications. This paper gives an overview of piezoelectric polymers based on their operating principle. This includes three main categories: bulk piezoelectric polymers, piezocomposites and voided charged polymers. State-of-the-art piezopolymers of each category are presented with a focus on fabrication techniques and material properties. A comparison between the different piezoelectric polymers and common inorganic piezoelectric materials (PZT, ZnO, AlN and PMN-PT) is also provided in terms of piezoelectric properties. The use of piezopolymers in different electromechanical devices is also presented. This includes tactile sensors, energy harvesters, acoustic transducers and inertial sensors.